Reshaping workspaces promoting mental health among BPO workers through an adaptable biophilic office in Ortigas - Cari, Maria Paulette Candice G.; Frederick C. Santos (Quezon City : College of Architecture, University of the Philippines Diliman, 2022)
BPO workers are one of the top office workers who experience mental health problems, this is due to their nature of work and the stress that come with it. This study aims to address these issues and at the same time adapt to the changes that the COVID-19 pandemic has brought about. The method focused on the research on the exploration of the needs of BPO employees, causes of their mental health issues, and office space design interventions for mental health, increasing job performance and productivity. The data shows that biophilic design greatly aids in improving a person’s well-being while flexible spaces are ideal for the changing work systems. These concepts were applied to the study, in addition, the concepts of placemaking, connectivity and maximizing reach are also used to create its design. The proposed project is an office design that mainly features the principles of biophilic design in the workspaces of the structure and the use of co-working spaces to be able to adapt to different work settings.
includes appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Office design -- Ortigas; Mental health facilities -- Employees -- Ortigas